Music and power in Confucius and Mao Zedong - Silva, Sofia Beatriz (2020)
For Mao Zedong and the Chinese Communist Party, musical activity has always been an important instrument of propaganda, serving as a modeling agent for the actions and ways of thinking, acting and feeling of the Chinese population throughout the various phases that make up Chinese history in the mid-20th century. The revolutionary songs, accessible to the general population through the education system and the various media available at the time, enabled the ideas and measures imposed by the Party to be conveyed more effectively, thus contributing to the consolidation of its power.